2013
DOI: 10.1371/journal.pone.0055407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Glutathione on Oxidative Liver Injury Induced by Dengue Virus Serotype 2 Infections in Mice

Abstract: The pathogenesis of dengue virus (DV) infection has not been completely defined and change of redox status mediated by depletion of glutathione (GSH) in host cell is a common result of viral infection. Our previous study has demonstrated that DV serotype 2 (DV2) infection alters host intracellular GSH levels, and exogenous GSH inhibits viral production by modulating the activity of NF-κB in HepG2 cells. GSH is the most powerful intracellular antioxidant and involved in viral infections. Thus, this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…E significantly prevented the oxidative stress induced by NDV challenge. Our results are consistent with several reported studies, in which authors had demonstrated an increase in oxidative stress by infection of different RNA viruses like influenza virus [11,12,43], hepatitis virus [44,45], human immunodeficiency virus [46], and dengue virus [47]. Infection of chickens with mesogenic NDV also showed the comparable results of decreased activities of CAT, GST and increased levels of MDA [17].…”
Section: Discussionsupporting
confidence: 93%
“…E significantly prevented the oxidative stress induced by NDV challenge. Our results are consistent with several reported studies, in which authors had demonstrated an increase in oxidative stress by infection of different RNA viruses like influenza virus [11,12,43], hepatitis virus [44,45], human immunodeficiency virus [46], and dengue virus [47]. Infection of chickens with mesogenic NDV also showed the comparable results of decreased activities of CAT, GST and increased levels of MDA [17].…”
Section: Discussionsupporting
confidence: 93%
“…The ability to shift the redox homeostasis of the host is shared by many other viruses, bacteria and protozoa. As shown in Table 1, many infections caused by intracellular pathogens result in a 2-4-fold decrease in the GSH: GSSG ratio of the host cell221222324252627282930313233. Importantly, this altered redox state is often utilized by the pathogen to facilitate its pathogenesis and/or transmission.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Wang et al, significantly elevated levels of TNF-a were observed in DENV type 2 infected mice, whereas reduced TNF-a levels were obtained in the presence of antioxidant. 39 This shows that the presence of antioxidants could inhibit the release of proinflammatory cytokines by inhibiting the virus-induced oxidative stress response and associated oxidative injury. The results of the present study support this concept by showing an elevated levels of MDA and the proinflammatory cytokine TNF-a upon dengue viral infection.…”
Section: Discussionmentioning
confidence: 99%